Effects of sodium alginate and rice variety on the physicochemical characteristics and 3D printing feasibility of rice paste. (June 2020) - Liu, Yuntao; Tang, Tingting; Duan, Songqi; Qin, Zhizhi; Li, Cheng; Zhang, Zhiqing; Liu, Aiping; Wu, Dingtao; Chen, Hong; Han, Guoquan; Lin, Bokun; He, Jialiang; et al.
Abstract: This paper investigated the 3D printing feasibility of rice (waxy rice, japonica rice, indica rice) paste and the effect of sodium alginate (SA) added at concentrations (0, 0.25%, 0.50%, 0.75%, 1.00%, w/w, dry rice flour basis) on the physicochemical and structural characteristics of rice paste. Results showed that rice paste incorporated with SA exhibited shear-thinning behavior so that it can be used as ideal material for 3D printing. The viscosity, degree of bound water and mechanical strength of rice paste increased with increasing addition of SA. When SA concentration was 0.50%, the 3D printed japonica rice product (3DJP3) provided the best printability and highest precision, followed by waxy rice product (3DWP3) and indica rice product (3DIP3). Scanning electron microscopy (SEM) revealed that more convolutions were induced in the 3D printed rice products upon the addition of SA, which increased the products stability. It was a further proof that 3DJP3 and 3DIP3 still maintained good structure and precision after steaming. However, 3DWP3 has swollen after steaming due to the highest amylopectin content of waxy rice and showed the worst shape fidelity. Overall, SA could be functioned as proper additives for 3D rice products, and the food matrix of proper types of rice and SA could be promising materials for 3D printing. Graphical abstract: Image 1 Highlights: Sodium alginate (SA) functioned as structural modifier in 3D printing of rice foods. Waxy, japonica and indica rice paste all achieved best printability at 0.50% SA. 3D waxy rice products after steaming have swollen due to high amylopectin content.